Technology of Creating A Virtual Laboratory of the Structure and Movements of Euglenoids from Biology on the Base of Computer Simulation Models (Eurasian Scientific Herald, 2023)
This article will discuss the development of models for computer simulation of laboratory work on the subject” Zoology". In particular, simulations are shown for the following Laboratories: the Laboratory of Invertebrate Zoology is an integral part of the theoretical course and is conducted in parallel. The subject of each study is the structural state of the object under study, as well as imitation of the object under study: the external structure, internal structure, movement, nutrition, reproduction and cyst of a unicellular animal.